PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI KASUS PERUSAHAAN MANUFAKTUR SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BEI TAHUN 2012-2016) - Oktala, Rosananda (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The research aims to prove the impact of the disclosure of corporate social responsibility on the financial performance of plastic and packaging manufacturing sub sector companies are listed on the Indonesian Stock Exchange (IDX) in 2012-2016. Company’s financial performance was measured by return on asset and return on equity. The population used in this study were all manufacturing companies in plastic and packaging sub sector which were listed in the IDX in 2012-2016. The research samples consisted of 6 companies from 30 observation and which were selected by using purposive sampling. The method of analysis being use in this research was simple linier regression and statistical t-test. The result showed that there are effect from disclosure of CSR on financial performance (measured by return on asset), with the p-value 0.030 ≤ 0.05 and there are no effect from disclosure of CSR on financial performance (measured by return on equity), with the the p-value 0.287 ≥ 0.05.